Treatment of Elopement Without Blocking With a Child With Autism. Issue 1 (January 2019) - Boyle, Megan A.; Keenan, Ginny; Forck, Kara L.; Curtis, Kaitlin S.
Elopement is a dangerous behavior common in children with autism spectrum disorder (ASD). Relative to other forms of problematic behavior, elopement has received little attention in both assessment and treatment. The current study entailed a functional analysis of elopement of one child with ASD, results of which suggested a partially automatic function. We then evaluated a differential reinforcement procedure, along with a rule, which successfully decreased elopement without the use of blocking. A changing-criterion design embedded within a withdrawal design was used to gradually increase the criterion for maintaining a close proximity to a therapist prior to being allowed to run.